PENGARUH PENDAPATAN PERKAPITA, PERTUMBUHAN EKONOMI DAN TARIF PAJAK TERHADAP TAX RATIO NEGARA ASEAN 2015-2021 - Annisa Shela Septiani; Sastradipraja, Usman (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The purpose of this study to analyze the effect of Percapita Income, Economic Growth Rate and Tax Rate on Tax Rations in ASEAN countries period 2015-2021. Quantitative is the method used in this study is. The population in this study are countries that are included in the ASEAN organization period 2015-2021. In this study, purposive sampling was used as a data collection technique with a sample 42 observation from 6 countries. This study used multiple linear regression analysis as an analysis teqnique. This research concluded that simultaneously variable percapita income, economic growth rate and tax rate has no effect on tax rations. Partially, variable percapita income has no effect, economic growth rate has no effect and tax rate has no effect on tax rations.